A comparative study on cisplatin analogs containing 7-azaindole (7AIH) and its seven halogeno-derivatives: Vibrational spectra, DFT calculations and in vitro antiproliferative activity. Crystal and molecular structure of cis-[PtCl2(4Br7AIH)2]·DMF. (15th November 2019) - Dysz, Karolina; Szmigiel-Bakalarz, Ksenia; Nentwig, Markus; Oeckler, Oliver; Malik-Gajewska, Magdalena; Turlej, Eliza; Michalska, Danuta; Morzyk-Ociepa, Barbara
Graphical abstract: Abstract: Eight platinum(II) complexes of the general formula cis -[PtCl2 (L)2 ] containing 7-azaindole (L = 7AIH) and its halogeno-derivatives: L = 3-chloro-7-azaindole (3Cl7AIH); 3-bromo-7-azaindole (3Br7AIH); 4-chloro-7-azaindole (4Cl7AIH); 4-bromo-7-azaindole (4Br7AIH); 5-bromo-7-azaindole (5Br7AIH); 3-bromo-4-chloro-7-azaindole (3Br4Cl7AIH) and 5-bromo-3-chloro-7-azaindole (5Br3Cl7AIH) were prepared. Two complexes, cis -[PtCl2 (3Br4Cl7AIH)2 ] (2 ) and cis -[PtCl2 (4Br7AIH)2 ]·DMF, are reported for the first time. Crystal structure of the latter compound has been determined with X-ray diffraction analysis (space group P 43, with a  = 14.775(2), c  = 41.640(8) Å, V  = 9090(3) Å 3 and Z  = 16). For all of these complexes, formation of the cis isomers in the solid state was confirmed by experimental vibrational (IR and Raman) spectroscopy combined with DFT calculations. A complete assignment of the IR and Raman spectra was made on the basis of the calculated potential energy distribution (PED). Stability of complex (2 ) in DMSO solution was investigated by FT-IR (ATR) spectroscopy. The in vitro antiproliferative activity of cis -[PtCl2 (3Br4Cl7AIH)2 ], cis -[PtCl2 (3Cl7AIH)2 ] and cis -[PtCl2 (3Br7AIH)2 ] was evaluated on selected human cancer cell lines and towards normal mouse fibroblast cell line (BALB/3T3). All complexes are more toxic than cisplatin against Es-2 (ovarian cancer), LNCaP (prostate adenocarcinoma) and MCF7 (breast cancer). Moreover, complex (2 ) is significantly more active than the other complexes on A549 (lung carcinoma, IC50  = 3.9 μM). However, the three investigated Pt(II) complexes with 7-azaindoles have revealed higher cytotoxicity against a normal cell line (BALB/3T3), in comparison to cisplatin.